Spatiotemporal Patterns of Meteorological Drought in the National Food Barn Region: A Case Study of South Sulawesi Province - Andini, Nastiti; Santikayasa, I Putu; Setiawan, Amsari Mudzakir (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2025)
Hydrometeorological disasters, particularly droughts, pose a significant threat to food crop productivity. South Sulawesi, one of Indonesia’s major rice-producing regions outside Java, is highly vulnerable to drought impacts. This study analyzes the spatiotemporal patterns of meteorological drought in South Sulawesi during 1981–2020 using the Standardized Precipitation Index (SPI) and applies run theory to characterize drought events. Monthly rainfall data were obtained from the Climate Hazards Center InfraRed Precipitation (CHIRP) dataset and complemented with ground-based observations from the BMKG rainfall observation network. Principal Component Analysis (PCA) with varimax rotation was employed to identify dominant spatial patterns of meteorological drought variability. The results identify three principal regions explaining more than 65% of the total variance: Region 1 (R1; 56%) in northern South Sulawesi, Region 2 (R2; 10%) in the central to eastern areas, and Region 3 (R3; 10%) in the western region. R1 exhibits the highest drought frequency and intensity but relatively short durations, whereas R3 shows the lowest frequency but the longest durations and largest magnitudes. A positive correlation between drought duration and magnitude is observed across all regions, along with a significant drying trend in the southern part of R2. Overall, these findings provide important insights into the spatial and temporal variability of meteorological drought in South Sulawesi and offer a scientific basis for strengthening drought risk management and regional food security strategies.